Novel Broadband Bandpass Filters Using Y-Shaped Dual-Mode Microstrip Resonators - Song, Kaijun; Xue, Quan (IEEE microwave and wireless components letters, 2009)
A Y-shaped dual-mode microstrip bandpass filter (BPF) with input-output cross-coupling is presented. The characteristic of the Y-shaped dual-mode resonator has been investigated. The resonance frequencies of the degenerate modes can be adjusted easily to satisfy the bandwidth of the BPF. A parallel-coupling feed structure with a cross coupling has been used to generate two transmission zeros at the lower and upper stopband, which can improve the out-of-band performance. A broadband dual-mode microstrip BPF has been designed, fabricated, and measured. The simulated and measured results are in agreement generally. Within the 3.1 to 5.4 GHz bandwidth, the measured insertion loss, return loss and group delay variation are below 0.5 dB, above 15 dB, and below 0.2 ns, respectively.